Welded design : theory and practice - Hicks, J. G. (John G.) (Abington Pub., 2001)
Welded design is often considered as an area in which there's lots of practice but little theory. Welded design tends to be overlooked in engineering courses and many engineering students and engineers find materials and metallurgy complicated subjects. Engineering decisions at the design stage need to take account of the properties of a material - if these decisions are wrong failures and even catastrophes can result. Many engineering catastrophes have their origins in the use of irrelevant or invalid methods of analysis, incomplete information or the lack of understanding of material behaviour. The activity of engineering design calls on the knowledge of a variety of engineering disciplines. With his wide engineering background and accumulated knowledge, John Hicks is able to show how a skilled engineer may use materials in an effective and economic way and make decisions on the need for the positioning of joints, be they permanent or temporary, between similar and dissimilar materials. This book provides practising engineers, teachers and students with the necessary background to welding processes and methods of design employed in welded fabrication. It explains how design practices are derived from experimental and theoretical studies to produce practical and economic fabrication. Provides specialist information on a topic often omitted from engineering coursesExplains why certain methods are used, and also gives examples of commonly performed calculations and derivation of data.